2011
DOI: 10.1242/dev.062703
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal remodeling and apoptosis require VCP-dependent degradation of the apoptosis inhibitor DIAP1

Abstract: SUMMARYThe regulated degeneration of axons or dendrites (pruning) and neuronal apoptosis are widely used during development to determine the specificity of neuronal connections. Pruning and apoptosis often share similar mechanisms; for example, developmental dendrite pruning of Drosophila class IV dendritic arborization (da) neurons is induced by local caspase activation triggered by ubiquitin-mediated degradation of the caspase inhibitor DIAP1. Here, we examined the function of Valosincontaining protein (VCP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 41 publications
5
68
0
Order By: Relevance
“…Interestingly, DIAP1 can be ubiquitylated for degradation itself (44,45). The proteolytic process of ubiquitylated DIAP1 remained unclear until a recent report suggesting that TER94-mediated UPS pathway is involved in this process (46). We have further shown in the present work that it is the dephosphorylated form of TER94 that is responsible for rapid DIAP1 degradation.…”
Section: Discussionsupporting
confidence: 47%
“…Interestingly, DIAP1 can be ubiquitylated for degradation itself (44,45). The proteolytic process of ubiquitylated DIAP1 remained unclear until a recent report suggesting that TER94-mediated UPS pathway is involved in this process (46). We have further shown in the present work that it is the dephosphorylated form of TER94 that is responsible for rapid DIAP1 degradation.…”
Section: Discussionsupporting
confidence: 47%
“…It has been reported that Drosophila inhibitor of apoptosis protein 1 (DIAP1; Thread -FlyBase) inhibits caspases through direct binding or degradation . Moreover, DIAP1 degradation leads to caspase activation and pruning, and DIAP1 stabilization interferes with this process (Rumpf et al, 2011). We therefore examined whether DIAP1 expression affected shaft extension absorbance in a manner similar to its affect on dendrite pruning.…”
Section: Diap1 Overexpression Delays Ectopic Shaft Extension Pruningmentioning
confidence: 99%
“…This process has been broadly termed axon degeneration and is intrinsic to the neuron. Despite their resemblance, axon degeneration and apoptosis are largely mechanistically distinct (1,3); however, axon and dendrite breakdown in the contexts of developmental pruning or trophic withdrawal does involve caspases and other apoptotic machinery (5,6,21). Components of the axon degeneration cascade include calpain proteases and the ubiquitin-proteasome system, and calcium influx is also an important step (7)(8)(9).…”
mentioning
confidence: 99%